HLA-F coding and regulatory segments variability determined by massively parallel sequencing procedures in a Brazilian population sample - Lima, Thálitta Hetamaro Ayala [UNESP]; Buttura, Renato Vidal [UNESP]; Donadi, Eduardo Antônio; Veiga-Castelli, Luciana Caricati; Mendes-Junior, Celso Teixeira; Castelli, Erick C. [UNESP] (Elsevier, 2016)
Human Leucocyte Antigen F (HLA-F) is a non-classical HLA class I gene distinguished from its classical counterparts by low allelic polymorphism and distinctive expression patterns. Its exact function remains unknown. It is believed that HLA-F has tolerogenic and immune modulatory properties. Currently, there is little information regarding the HLA-F allelic variation among human populations and the available studies have evaluated only a fraction of the HLA-F gene segment and/or have searched for known alleles only. Here we present a strategy to evaluate the complete HLA-F variability including its 5′ upstream, coding and 3′ downstream segments by using massively parallel sequencing procedures. HLA-F variability was surveyed on 196 individuals from the Brazilian Southeast. The results indicate that the HLA-F gene is indeed conserved at the protein level, where thirty coding haplotypes or coding alleles were detected, encoding only four different HLA-F full-length protein molecules. Moreover, a same protein molecule is encoded by 82.45% of all coding alleles detected in this Brazilian population sample. However, the HLA-F nucleotide and haplotype variability is much higher than our current knowledge both in Brazilians and considering the 1000 Genomes Project data. This protein conservation is probably a consequence of the key role of HLA-F in the immune system physiology.
Keywords: Haplotypes; HLA-F; MHC; Next Generation Sequencing; NGS; Polymorphisms; Variability